Hubungan Antara Asupan Makanan Terhadap Diabetes Mellitus Tipe 2: Sebuah Studi Pustaka - Putu Arya Indira Prameswari; Reni Zuraida (CV. Jasa Sukses Abadi, 2023)
Type 2 diabetes mellitus (DMT2) is a global health problem with a significant impact on life. The prevalence of DM in the world reached 537 million people in 2021. DMT2 is a metabolic disorder caused by increased blood glucose levels. One of the risk factors DMT2 is dietary intake. Dietary intake is the main cause of the rapid increase in the incidence of DM in developing countries. Blood glucose levels are mainly influenced by dietary carbohydrates, high intake of fast food, carbonated drinks, intake of red meat, sweet foods and excessive intake of white rice are also thought to contribute to an increased risk of insulin resistance in DMT2. Based on this, the author are interested in conducting a literature study about the relationship between dietary intake and type 2 diabetes mellitus. Based on the literature study, it can be concluded that there is a significant relationship between dietary intake and DMT2 so that food intake can affect the incidence of DMT2 in individuals. Various types of dietary components can affect the risk of developing DMT2, therefore healthy dietary intake and regular diet patterns can be done to reduce the risk of various diseases.